Legal Protection of Consumers in Case of Bad Credit: Consumer and Banking Law Perspective - Azzahra, Mutiara; Rato, Dominikus; Susanti, Dyah Ochtorina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research discusses consumer protection in cases of credit congestion in Indonesia, with a focus on improving law enforcement as one of the key aspects in ensuring adequate protection for consumers. In this context, effective law enforcement is crucial to protecting consumer rights and maintaining the integrity of the financial system as a whole. This research identifies several strategic steps that can be taken to strengthen law enforcement against financial institutions that violate consumer protection regulations. The results of this research are: First, it is necessary to increase supervision and law enforcement from financial supervisory authorities, such as Bank Indonesia and OJK, through routine audits, surprise inspections, and strengthening authority. Second, cooperation between financial supervisory authorities and law enforcement such as the police and prosecutors is important to increase the effectiveness of law enforcement.